The Implementation of Inclusive Education by English Teachers to Teach Slow Learners at SMK Negeri 3 Singaraja - Cintya Maha Yekti; Ni Made Ratminingsih; Kadek Sintya Dewi (Journal of Psychology and Instruction, 2019)
Inclusive education has been increasing significantly in Singaraja and helping the students with special needs as well as getting their right to have a proper education. Since inclusive was a new policy in education, new research was needed to find out how the implementation and the obstacles faced in inclusive. This study was aimed at investigating the implementation of inclusive education by English teachers to teach slow learners included in a regular classroom. This research was conducted at SMK Negeri 3 Singaraja as one of the general schools which implemented inclusive education. This research was in the form of qualitative research with a case study method. The data were obtained through document study, interviews, and observations. The findings show that (1) the English teachers used same teachers' preparation and modified some activities in the learning process and used different assessment, and (2) there were also found supporting factors such as complete administration, a good way of transferring knowledge, used different assessment and also found challenging factors in implementing inclusive education such as lack of trained teacher, lack of inclusive policy, and lack of differentiation in instructions. Inclusive education has been implemented at SMK Negeri 3 Singaraja but still has to be improved.